Electrical stimulation of coleopteran muscle for initiating flight - Choo, Hao Yu (2018)
Some researchers have long been interested in reconstructing natural insects into steerable robots or vehicles. However, until recently, these so-called cyborg insects, biobots, or living machines existed only in science fiction. Owing to recent advances in nano/micro manufacturing, data processing, and anatomical and physiological biology, we can now stimulate living insects to induce user-desired motor actions and behaviors. To improve the practicality and applicability of airborne cyborg insects, a reliable and controllable flight initiation protocol is required. This study demonstrates an electrical stimulation protocol that initiates flight in a beetle (Mecynorrhina torquata, Coleoptera). A reliable stimulation protocol was determined by analyzing a pair of dorsal longitudinal muscles (DLMs), flight muscles that oscillate the wings. DLM stimulation has achieved with a high success rate (> 90%), rapid response time (< 1.0 s), and small variation (< 0.33 s; indicating little habituation). Notably, the stimulation of DLMs caused no crucial damage to the free flight ability. In contrast, stimulation of optic lobes, which was earlier demonstrated as a successful flight initiation protocol, destabilized the beetle in flight. Thus, DLM stimulation is a promising secure protocol for inducing flight in cyborg insects or biobots.